Estudo etnofarmacológico e avaliação de atividades antinociceptiva de plantas medicinais da comunidade quilombola Mussuca, Laranjeiras/SE - Klank, Francisco Albuquerque (2014)
The use of medicinal plants is present since the ancient times of civilization, currently being used as a complement in the treatment of pathologies. In Sergipe, more specifically in Mussuca community in Orange, the use of medicinal plants is closely linked to the cultural aspects of the community. Medicinal plants in Mussuca can be found in large quantities in the backyards of residents. Even as this massive amount of medicinal plants from various genres, few studies of pharmacological prospecting etnodirigida performed in maroon territories. In this sense, this work was to carry out an ethnopharmacological survey of medicinal plants with antinociceptive properties in maroon community Mussuca and is presented in three chapters. In the first chapter described the general introduction, objectives and literature review. In the second chapter an ethnobotanical survey was presented from popular knowledge for the identification of medicinal plants used in the antinociceptive activity Mussuca community in pain management. And in the third chapter a pharmacological study was conducted to identify the antinociceptive effect of the six plants indicated primary use by local experts. The ethnobotanical data were collected through participant observation and semi-structured interviews. In parallel, we applied the snow ball method in which it was possible to identify seven local experts, where each expert indicated an analgesic plant primary use. The quantitative ethnobotanical data were analyzed using the technique use value and the qualitative results were analyzed using the technique collective subject discourse. We conclude that the experts of the village have empirical knowledge about medicinal plants and technical analgesic use value helped identify the species of greatest significance to the community. For pharmacological testing of the writhing test was performed to identify the antinociceptive effect of plant species by reducing the writhing. The results were analyzed by 1-way ANOVA followed by Bonferroni test. The program used was Graph Pad Prism version 4.0. It was found that all the medicinal plants has antinociceptive effect, with the more potent the Schinus terebinthifolius Raddi, more effective Rolandra fruticosa (L.) Kuntze, Guarea guidonia, Cecropia pachystachya Trécul, Schinus terebinthifolius Raddi.